Pengaruh Media Booklet terhadap Peningkatan Pengetahuan tentang Anemia Remaja Putri - Efni, Nel; Fatmawati, Tina Yuli (Prosiding Seminar Kesehatan Nasional, 2023)
Two Million people in the world or more than 30% of the world's population suffer from anemia, especially due to iron deficiency. Anemia can affect anyone, including teenagers. Anemia causes blood to not bind and transport enough oxygen from the lungs to the rest of the body. If the oxygen needed is not enough, it will result in difficulty concentrating so that learning achievement decreases. The aim of this research is to determine the effect of booklet media in increasing knowledge about anemia in adolescents at SMP N 19 Jambi City. This research is a pre-experimental research that uses One Group Pre Test and Post Test. Sampling was taken using Proportionate sampling, totaling 35 people. Data were analyzed univariately and bivariately using the T Test statistical test. The research results showed that there was an influence of booklet media in increasing knowledge about anemia in young women at SMP N 19 Jambi City with a value (p value <0.005). Booklet media as an effective medium can be used to convey information, especially about anemia